Brian Drain of China: The Inclination of Chinese Students to Stay Abroad After Their Studies - Bai, Yuna (2013)
The topic of brain drain and brain gain has flourished over the years in China. Many existing literatures have reviewed the trend on brain drain and its impact on the economic development of the source countries and the host countries. This research is to investigate this subject based on the theoretical lens of human capital. This research adopts the quantitative method, to conduct a survey for three months on 300 Chinese overseas students in Malaysian universities. The collected data will be analyzed using both SPSS (frequency distribution) software and Smart PLS software (convergent and discriminat validity and path coefficients test). This research takes four independent variables which include satisfaction with the university; social support; family tie and career perception. The dependent variable is the intention of staying abroad after graduation by respondents. The findings reveal that social support from the university in host country and career perception at home and host country do impact and influence the Chinese students stay abroad, after their graduation. The implication of the findings is to reverse brain drain, and for the Chinese government to improve their education quality and better the relationship between the university and the students. The policies maker like HR department should enhance the employment environment and help create career development prospect for the domestic talents and for potential returnees.